Activation of Matrix-Metalloproteinase-2 and Membrane-Type-1-Matrix-Metalloproteinase in Endothelial Cells and Induction of Vascular Permeability In Vivo by Human Immunodeficiency Virus-1 Tat Protein and Basic Fibroblast Growth Factor - Toschi, Elena (The American Society for Cell Biology, 2001)
Previous studies indicated that the Tat protein of human immunodeficiency virus type-1 (HIV-1) is a progression factor for Kaposi's sarcoma (KS). Specifically, extracellular Tat cooperates with basic fibroblast growth factor (bFGF) in promoting KS and endothelial cell growth and locomotion and in inducing KS-like lesions in vivo. Here we show that Tat and bFGF combined increase matrix-metalloproteinase-2 (MMP-2) secretion and activation in endothelial cells in an additive/synergistic manner. These effects are due to the activation of the membrane-type-1-matrix-metalloproteinase and to the induction of the membrane-bound tissue inhibitor of metalloproteinase-2 (TIMP-2) by Tat and bFGF combined, but also to Tat-mediated inhibition of both basal or bFGF-induced TIMP-1 and -2 secretion. Consistent with this, Tat and bFGF promote vascular permeability and edema in vivo that are blocked by a synthetic MMP inhibitor. Finally, high MMP-2 expression is detected in acquired immunodeficiency virus syndrome (AIDS)-KS lesions, and increased levels of MMP-2 are found in plasma from patients with AIDS-KS compared with HIV-uninfected individuals with classic KS, indicating that these mechanisms are operative in AIDS-KS. This suggests a novel pathway by which Tat can increase KS aggressiveness or induce vasculopathy in the setting of HIV-1 infection.